Stereogenic π-Conjugated Macrocycles: Synthesis, Structure, and Chiroptical Properties Including Circularly Polarized Luminescence - Hasegawa, Masashi; Mazaki, Yasuhiro (Synlett, 2023)
Highly symmetrical and aesthetically pleasing molecules have attracted the attention of organic chemists. We synthesized new highly symmetric stereogenic π-conjugated macrocycles with planar or axial chirality. Macrocyclic oligomers synthesized by Yamamoto coupling or Suzuki–Miyaura cross-coupling from the π-unit containing chirality. These cyclization reactions gave multiple oligomers in relatively high yields. We then elucidated their structures and investigated their chiroptical properties, including circular dichroism (CD) and circularly polarized luminescence (CPL). Because of the selection rule for rigid and symmetric structures, these macrocycles exhibit a high dissymmetry factor (gabs or glum) for circularly polarized light in CD or CPL. Several rigid cyclic compounds retain a highly symmetric structure in the excited state and exhibit higher glum values than common chiral organic compounds. This Account provides a brief background regarding chiroptical properties, followed by a summary of the various macrocycles synthesized in this study. We are glad if this Account will be a source of ideas not only for chemists working with π-conjugated compounds, but also for synthetic chemists working with chiral compounds, especially those engaged in asymmetric synthesis.1 Introduction2 Brief Description of Chiroptical Properties3 Stereogenic Macrocycle Based on [2.2]Paracyclophane3.1 Stereogenic Double-decker Oligothiophene3.2 Stereogenic Biselenophene Macrocycle3.3 Helical Oligophenylene Linked with [2.2]Paracyclophane4 Stereogenic Macrocycle Based on Binaphthyl4.1 Cyclic Oligomer of Chiral Binaphthyl4.2 Doubly Twisted Binaphthyl Dimer4.3 Cyclic Oligomer of Binaphthyl Extended with Paraphenylene4.4 Curved Helical Paraphenylene Anchoring Chiral Binaphthyl4.5 Binaphthyl-Hinged [5]-Helicene5 Summary
Keywords: macrocycle; chirality; circularly polarized luminescence; [2.2]paracyclophane; binaphthyl; oligothiophene; paraphenylene; helicene